EFEKTIVITAS PENGELOLAAN ANGGARAN PENDAPATAN DAN PENGELUARAN DESA DI DESA SELAAWI KABUPATEN TALEGONG KABUPATEN GARUT - Widdy Yuspita Widiyaningrum; Wiguna (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
The Village Revenue and Expenditure Budget is the village government's annual financial plan which is discussed and agreed upon by the village government and the Village Consultative Body. With the Covid-19 pandemic, various policies were made to accelerate the prevention of the spread of COVID-19 down to the village level. The government issued Ministerial Regulation Number 7 of 2020, the Second Amendment, which regulates changes in village fund priorities for Covid-19 response, Village cash labor-intensive, Direct assistance cash. The purpose of this research is to find out and understand the effectiveness of the program by using the theory of Martani and Lubis (1987) through three approaches, the first is the source approach, the second is the process approach, and the third is the target approach. The method used in this research is qualitative with a descriptive analysis approach. Data were collected by observation, interviews and documentation. In the process of collecting data, the researcher involved several village officials who became the object of research, then the data that had been obtained was processed and analyzed after that it was interpreted. The results of this study indicate that the village has implemented the use of the 2020 budget, namely the prevention and handling of covid-19, cash labor-intensive, and direct cash assistance by changing/shifting the development budget. The effectiveness of budget absorption obtained from the results of this study shows the level of achievement of the Village Government's performance in preventing and handling Covid-19, cash labor-intensive and direct cash assistance. The Village Government has implemented an effectiveness level, although not perfect. Management of the Village Revenue and Expenditure Budget must be more effective, it is necessary to improve the quality of village apparatus human resources, especially the village head, the head of village financial affairs, and the activity implementation team, and convey the aspirations of the village government to the central government.